Microchannel flow fields for polymer electrolyte fuel cells - Chivengwa, Tapiwa (Department of Chemical Engineering, 2015)
Fuel cell technology represents an efficient and relatively quiet way of generating electricity. Among the various types of fuel cells, the polymer electrolyte fuel cell (PEFC) is the leading candidate for portable, automotive and more recently stationary applications. One of the key challenges affecting both the performance and durability of low temperature PEFCs is water management. Various water management strategies in PEFCs have been employed to date ranging from manipulation of operating conditions, fuel cell component design and flow field design to name a few. The optimisation of the flow field design for water removal has primarily focused on the use of flow channels which are in the minichannel range. This study investigated the use of a microchannel flow field design (channel hydraulic diameters of less than or equal to 200 ìm) for a low temperature PEFC. Specifically it focused on the effect of using a microchannel design on overall fuel cell performance, pressure drop and the cell voltage behaviour over time. In addition the effect of different operating conditions was also investigated. The overall aim was to develop a more comprehensive understanding of the use of a microchannel based flow field system with specific focus on water management. Fuel cell testing of two different flow field designs, namely a microchannel design and a more conventional commercial minichannel design, was performed in a single cell set up. Two operating conditions, cathode flow rate and cell compression, were varied and the effect on overall fuel cell performance and limiting current was investigated. Several diagnostic measurements including polarization curve, high frequency resistance, electrochemical impedance spectroscopy, pressure drop co-efficient and cell voltage monitoring were conducted to understand the water management behaviour and trends in the two different aforementioned flow field designs.